2003
DOI: 10.1093/jn/133.11.3428
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women Differ in Lipoprotein Response to Dietary Saturated Fat and Cholesterol Restriction

Abstract: A diet restricted in saturated fat and cholesterol is recommended for subjects with elevated LDL cholesterol concentrations before and during drug therapy. Gender differences in lipoprotein subspecies response to such diets have not been studied in detail. We examined the effects of a diet low in total fat, saturated fat and cholesterol (Therapeutic Lifestyle Changes, TLC, diet: 26% of energy as fat, 4% as saturated fat, and 45 mg cholesterol/4.2 MJ), compared with an average American diet (AAD: 35% of energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 32 publications
2
50
1
2
Order By: Relevance
“…12,13 Despite similar intervention-control group differences in the composition of the diet throughout the years, 16 the follow-up has consistently shown significant cholesterol-lowering effects only in boys. Some [35][36][37][38] but not all 39 earlier studies in adults have suggested that men show greater changes than women in LDL cholesterol concentration in response to changes in dietary intake of saturated fatty acids. The mechanism for the possible higher resistance to diet-induced LDL lowering in females is unknown but may relate to differences in sex hormone levels.…”
Section: Discussionmentioning
confidence: 96%
“…12,13 Despite similar intervention-control group differences in the composition of the diet throughout the years, 16 the follow-up has consistently shown significant cholesterol-lowering effects only in boys. Some [35][36][37][38] but not all 39 earlier studies in adults have suggested that men show greater changes than women in LDL cholesterol concentration in response to changes in dietary intake of saturated fatty acids. The mechanism for the possible higher resistance to diet-induced LDL lowering in females is unknown but may relate to differences in sex hormone levels.…”
Section: Discussionmentioning
confidence: 96%
“…16 For example, the likelihood to seek medical attention and, if procured, the extent and intensity of the medical intervention could affect the outcome of these studies. 23,24 Moreover, the general underrepresentation of women in large clinical trials 25,26 prevents global interpretation of published results.…”
Section: Clinical Impact Of Sex and Congestive Heart Failurementioning
confidence: 99%
“…147 Moreover, in middle-aged and elderly subjects, men respond to restriction in total fat, saturated fat, and cholesterol differently than women. 24 To further complicate matters, plasma triglycerides are better predictors of cardiovascular risk in women, whereas the LDL cholesterol concentration is a stronger predictor in men. 78,150,151 However, this discrepancy disappears in older, postmenopausal women in whom LDL levels exceed those in men and become better correlated with cardiovascular risk.…”
Section: Estrogen Phytoestrogens and Lipid Metabolismmentioning
confidence: 99%
“…Restriction of saturated fatty acids reduces TC and LDL-C, as well as HDL-C, and the latter is effective especially in women [80][81][82][83] ; 2) omega 3 polyunsaturated fatty acids inhibit the hepatic secretion of VLDL and, thus, increase HDL-C. Omega 6 fatty acids reduce these levels by reducing apoA-I production and by increasing HDL catabolism; 3) monounsaturated fatty acids induce HDL-C elevation by reducing VLDL secretion; 4) unsaturated fatty acids, in transform, enhance apoA-I catabolism and, thus, reduce HDL-C 84 ; 5) carbohydrates reduce HDL-C by increasing its catabolism as well as the secretion of VLDL. Recently, Aude et al 85 ; showed that reduced ingestion of simple carbohydrates and an increased ingestion of complex carbohydrates, associated to an increase of mono-unsaturated fatty acids, result in a less marked reduction of HDL-C in comparison with the Phase 1 diet recommended by NCEP 31 .…”
Section: Dietary Habitsmentioning
confidence: 99%